2009
DOI: 10.1007/s11367-009-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in a carbon footprint model for detergents; quantifying the confidence in a comparative result

Abstract: Background, aim, and scope A new trend driven by climate change concerns is the interest to label consumer products with a carbon footprint (CF) number. Here, we present a study that examines the uncertainty in the estimated CFs of a liquid and a compact powder detergent and how the uncertainty varies with the type of comparison one wishes to make. Materials and methods A simplified CF model for detergents, encompassing all life cycle stages, has been used for the calculation of CFs. The CFs for the two deterg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 11 publications
0
52
0
Order By: Relevance
“…This study focused on data variability and uncertainty and, to some extent, model uncertainty in the methods used to quantify the emissions at farm level. However, model and data uncertainty cannot be clearly divided (Koning et al 2010). For example, the data from aggregated background processes, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…This study focused on data variability and uncertainty and, to some extent, model uncertainty in the methods used to quantify the emissions at farm level. However, model and data uncertainty cannot be clearly divided (Koning et al 2010). For example, the data from aggregated background processes, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al [43] compared three carbon labels from Singapore, the U.S., and UK and found that although these carbon labels are based on the LCA method, comparisons cannot be made because many transparency issues, such as system boundary, unit of measurement and accredited evaluation, vary significantly across the these three carbon labels. Koning et al [21] provided an example showing how increasing the discretion of choosing system boundaries in LCA studies can result in misleading results. Manufacturers can manipulate data in the operational stage to create "low carbon" products.…”
Section: Discussionmentioning
confidence: 99%
“…For example, parameters may be used in scenarios or choices may be made in models. de Koning et al 21 have noted that these three types of uncertainty manifest themselves by contributing to the uncertainty of the final result of an aggregated cradle-to-gate LCA. They correctly point out that all forms of uncertainty are expressed as uncertainty in a parameter value, even though it is actually an aggregate of parameter, model, and scenario uncertainty.…”
Section: Definitions Of Quantities In Life Cycle Assessmentsmentioning
confidence: 99%
“…although it is technically feasible and certainly has been done. 21,23 When the influence of these is convolved through weighting, important information about their impact is masked and lost.…”
Section: Definitions Of Quantities In Life Cycle Assessmentsmentioning
confidence: 99%